Navigating Calcium and Reactive Oxygen Species by Natural Flavones for the Treatment of Heart Failure - Yu, Tianhao; Huang, Danhua; Wu, Haokun; Chen, Haibin; Chen, Sen; Cui, Qingbin (Frontiers in Pharmacology, 2021)
Heart failure (HF), the leading cause of death among men and women world-wide, causes great health and economic burdens. HF can be triggered by many factors, such as coronary artery disease, heart attack, cardiomyopathy, hypertension, obesity, etc., all of which have close relations with calcium signal and the level of reactive oxygen species (ROS). Calcium is an essential second messenger in signaling pathways, playing a pivotal role in regulating the life and death of cardiomyocytes via the calcium-apoptosis link mediated by the cellular level of calcium. Meanwhile, calcium can also control the rate of energy production in mitochondria that are the major resources of ROS whose overproduction can lead to cell death. More importantly, there are bidirectional interactions between calcium and ROS, and such interactions may have therapeutic implications in treating HF through finely tuning the balance between these two by certain drugs. Many naturally derived products, e.g., flavones and isoflavones, have been shown to possess activities in regulating calcium and ROS simultaneously, thereby leading to a balanced microenvironment in heart tissues to exert therapeutic efficacies in HF. In this mini review, we aimed to provide an updated knowledge of the interplay between calcium and ROS in the development of HF. In addition, we summarized the recent studies (in vitro, in vivo and in clinical trials) using natural isolated flavones and isoflavones in treating HF. Critical challenges are also discussed. The information collected may help to evoke multidisciplinary efforts in developing novel agents for the potential prevention and treatment of HF.